Efficiency–Resilience Analysis of Indian Public Sector Banks - Preet, Anmol; Khurana, Ajay (Prabandhan: Indian Journal of Management, 2026)
Purpose : This research assessed the technical efficiency (TE) and resilience of the key Indian public sector banks under normal and abnormal circumstances. Design/Methodology/Approach : The study is an empirical quantitative research using secondary data from 2012 to 2023. We calculated TE using the input-oriented constant return to scale model of data envelopment analysis (DEA). We also developed two indicators for measuring the impact of disruption and recovery, representing the short-term effects of shocks and recovery. We validated the results using various statistical methods. Findings : The study revealed that the State Bank of India was fully and continuously efficient with high resilience against shocks. The Bank of Baroda had complete resilience, while the Punjab National Bank remained poor. Other banks had moderate resilience with some stability. Practical Implications : The findings highlighted the importance of governance quality, asset management, and digital preparedness in strengthening resilience. They also offered insights to regulators and policymakers to regulate stability and resilience in banking. Originality/Value : The study provided a new insight into efficiency measurement with the inclusion of resilience in the form of two new measures that capture the impact of short-term shocks and long-term recovery, respectively.